Optical detection of paramagnetic centres in activated oxyfluoride glass-ceramics - Rogulis, Uldis T.; Fedotovs, Andris; Antuzevics, Andris; Berzins, Dzintars; Zhydachevskyy, Yaroslav; Sugak, D. (Polish Academy of Sciences, 2018)
Electron paramagnetic resonance (EPR), magnetic circular dichroism (MCD) and EPR detected via MCD (MCD-EPR) investigations have been performed on rare-earth activated oxyfluoride glasses and glass-ceramics. Er3+, Gd3+, and Mn2+ activators in oxyfluoride glass-ceramics show paramagnetic MCD behaviour and the MCD-EPR has been detected. The results of the MCD-EPR measurements for the Er-doped oxyfluoride glass-ceramics showed that Er3+ ions in the CaF2 crystallites in these ceramics embed only in the cubic symmetry environment, similarly to the previous observations of cubic Gd3+ centres in the glass-ceramics containing CaF2. Finally, the correlation of optics and paramagnetic centres is discussed for Mn-doped YAlO3 ceramics.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics